Sistem Otomasi Lazy Minting NFT di Marketplace Rarible pada Blockchain Ethereum Menggunakan Autoit - Alfin Abdilah; Putri Anggun Sari; Ananto Tri Sasongko (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
This research is motivated by the difficulty of the Lazy Minting NFT process in the Rarible Marketplace. The NFT Lazy Mining process on the Rarible Marketplace can be said to be inefficient because the process still has to be done one by one. Not to mention other problems that arise such as wrong numbering and typing errors or typos. This resulted in the Lazy Minting NFT process on the Rarible Marketplace becoming less effective. This problem will make it difficult for NFT creators if they have a large number of digital works. Therefore, this research aims to build an automated NFT Lazy minting system on the Rarible Marketplace on the Ethereum Blockchain using AutoIt, so that the NFT Lazy minting process on the Rarible Marketplace becomes more effective and efficient. The method used in the development of the Lazy Minting NFT automation system in the Rarible Marketplace is Agile Development. This research resulted in a Lazy minting NFT automation system on the Rarible Marketplace on the Ethereum Blockchain. The conclusion of this study is that the application of this system is able to make the NFT Lazy mining process on the Rarible Marketplace more effective and efficient. This can make it easier for NFT creators in their NFT sales process.